تحديات منهج تعليم اللغة العربية في التعليم العالي (دراسة حالة في الجامعة الإسلامية تريبكتي ليربايا كديري) - Arwan Rifa'i; Anwar Rudi (BARA AJI: Jurnal Keilmuan Bahasa Arab dan Pengajarannya, 2025)
This research aims to identify the challenges in the Arabic language teaching curriculum at the Islamic University of Tribakti Lirboyo Kediri and solutions to address these challenges. This research uses a qualitative approach with a descriptive style by analyzing phenomena that occur in the field systematically, realistically, and accurately. The results of this research indicate that the challenges in the Arabic language teaching curriculum at the Islamic University of Tribakti Lirboyo Kediri consist of several issues: the incompatibility of the national curriculum with local needs, limited industry participation in the curriculum, non-innovative teaching approaches, lack of qualified teaching staff, insufficient teaching materials, limited use of technology in Arabic language teaching, and low student motivation. The solutions to these challenges are: integrating the national curriculum with local needs through periodic needs analysis, improving teacher competencies through courses and workshops, developing contextual and digital teaching materials to increase the interactivity of the learning process, improving technological infrastructure and training professors on using technology, and adapting the curriculum and interactive teaching methods to increase their relevance and motivate students.